Preliminary Characterization, Antioxidant Properties and Production of Chrysolaminarin from Marine Diatom Odontella aurita - Song Xia; Baoyan Gao; Aifen Li; Jihai Xiong; Ziqiang Ao; Chengwu Zhang (Marine Drugs, 2014)
A new chrysolaminarin, named CL2, with a molecular mass of 7.75 kDa, was purified from the marine diatom, Odontella aurita, using DEAE-52 cellulose anion-exchange chromatography and Sephadex G-200 gel-filtration chromatography. The monosaccharide and structural analysis revealed that CL2 was a glucan mainly composed of glucose, which was linked by the β-d-(1→3) (main chain) and β-d-(1→6) (side chain) glycosidic bond, demonstrated by infrared spectroscopy (IR) and nuclear magnetic resonance (NMR). The antioxidant activity tests revealed that the CL2 presented stronger hydroxyl radical scavenging activity with increasing concentrations, but less was effective on reducing power analysis and scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. The influences of nitrogen concentration and light intensity on chrysolaminarin production of O. aurita were further investigated in a glass column photobioreactor, and a record high chrysolaminarin productivity of 306 mg L−1 day−1 was achieved. In conclusion, the chrysolaminarin CL2 from O. aurita may be explored as a natural antioxidant agent for application in aquaculture, food and pharmaceutical areas.